IMPROVING STUDENTSâ€™ READING COMPREHENSION OF DESCRIPTIVE TEXT THROUGH COLLABORATIVE MURDER - Asrifan, Andi; Nadira, Nadira; Haedar, Haedar (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
The objectives of the research was to find out whether or not teaching of descriptive text through collaborative â€œMURDERâ€ improve studentsâ€™ reading comprehension at the Eighth grade students of SMP Negeri 2 Pancarijang, and to find out whether or not the studentsâ€™ attitude in teaching of descriptive text through collaborative â€œMURDERâ€ technique of reading comprehension at the Eighth students of SMP Negeri 2 Pancarijang. This research employed pre-experimental method that applied pre-test and post-test. The population was the Eighth grade students of SMP Negeri 2 Pancarijang. Total number of population was 131 students and one class of them were taken as sample by using cluster sampling technique, class VIII6 was sample. Total number of sample was 20 students. The instrument used in this research were reading comprehension test and questionnaire. The result of this research showed that the mean score of the students in the post-test (79,60) was greater than pre-test (55,00). This showed that there was significant difference between the students who were taught by using collaborative â€œMURDERâ€ technique in descriptive text in reading comprehension. The result in pre-test and post-test that the p-value was lower than the df (0,000<0,05). This meant that H1 was accepted. The study concluded that teaching reading comprehension by using collaborative â€œMURDERâ€ improved the studentsâ€™ to read descriptive text at the Eighth grade students of SMP Negeri 2 Pancarijang